Impact of structured reporting of lower extremity CT angiography on report quality and workflow efficiency - Melzig, Claudius; Mayer, Victoria Louise; Moll, Martin; Naas, Omar; Hartmann, Sibylle; Do, Thuy; Kauczor, Hans-Ulrich; Rengier, Fabian (Diagnostics, 2024)
We assessed the effects of structured reporting (SR) of lower extremity CT angiography (CTA) on report quality and workflow efficiency compared with conventional reports (CR). Surveys were conducted at an academic radiology department before and after the introduction of an SR template. Participants (n = 39, 21) rated report quality and report creation effort (1: very dissatisfied/low to 10: very satisfied/high) and whether SR represents an improvement over CR (1: completely disagree to 5: completely agree). Four residents and two supervising radiologists created both CR and SR of 40 CTA examinations. Report creation time was measured and the factual accuracy of residents’ reports was judged. Report completeness (median 8.0 vs. 7.0, p = 0.016) and clinical usefulness (7.0 vs. 4.0, p = 0.029) were rated higher for SR. Supervising radiologists found report clarity improved by SR (8.0 vs. 4.5, p = 0.029). Report creation effort was unchanged (7.0 vs. 6.0, p > 0.05). SR was considered an improvement over CR (median 4.0, IQR,3.0-5.0). Report supervision was shortened by SR (6.2 ± 2.0 min vs. 10.6 ± 3.5 min, p < 0.001) but total time for report creation remained unchanged (36.6 ± 12.8 min vs. 36.4 ± 11.0 min, p > 0.05). Factual accuracy of residents’ SR was deemed higher (8.0/9.5 vs. 7.0/7.0, p = 0.006/ < 0.001). In conclusion, SR has the potential to improve report quality and workflow efficiency for lower extremity CTA.
Gesehen am 05.02.2025